A human-machine interactive hybridized biomechanical nanogenerator as a self-sustainable power source for multifunctional smart electronics applications. (October 2020) - Rana, S M Sohel; Rahman, M. Toyabur; Salauddin, M.; Maharjan, P.; Bhatta, T.; Cho, Hyunok; Park, Jae Yeong
Abstract: Biomechanical energy harvesting has been attracting increased attention for powering electronic devices and reducing battery dependency. Here, we report a human–machine interactive hybridized biomechanical nanogenerator (HMI-HBNG) including an electromagnetic generator (EMG) using a Halbach magnet array and an interdigitated electrode-based triboelectric nanogenerator (TENG). The Halbach magnet array enhances the magnetic flux density, increasing the output power of the EMG eightfold. Introducing a nanowire structure in a polytetrafluoroethylene (PTFE) film and incorporating a novel phase inversion technique for microstructure modifications in the nylon/11 film increase the energy harvesting efficiency of the TENG. The performance of the HMI-HBNG is investigated from different perspectives and shows a maximum output power density of 185 W/m 2 across an optimum load resistance of 1.6 kΩ at 5 Hz under 20 m/s 2 acceleration. In a human motion experiment, the HMI-HBNG charges a Li-ion battery (18 mAh) from 0 V to 3 V in approximately 10 s and operates multiple electronics devices simultaneously for 3 min. By using a customized power management circuit, the HMI-HBNG can provide a self-sustainable power source for driving multifunctional smart electronic devices, including Bluetooth computer mice, smartwatches, and smartphones. This work represents significant progress toward a self-powered system and practical power source. Graphical abstract: Image 1 Highlights: A dual Halbach array magnetic arrangement was employed in EMG which increasing the output power by eightfold. A novel phase inversion technique was applied for microstructure surface modifications in the nylon/11 film of the TENG. The fabricated HMI-HBNG exhibited a maximum output power density of 185 W/m 2 across an optimum load resistance of 1.6 kΩ. The HMI-HBNG can run continuously five low-power electronics devices for 180 s after 10 s of Li-ion battery charging. The proposed hybridized nanogenerator was successfully demonstrated as a self-powered Bluetooth computer mouse.